EMPOWERMENT OF FARMER GROUPS THROUGH THE UTILIZATION OF BACKYARD GARDENS FOR THE CULTIVATION OF CASH CROPS TO SUPPORT FOOD SECURITY: A LITERATURE REVIEW IN PAYA PASIR VILLAGE: Empowerment of Farmer Groups, Plantation Crop Cultivation, Food Security - Turino Januar Budyanto (Jurnal Ilmiah METADATA, 2026)
Household food security in urban coastal areas such as Paya Pasir Village, Medan Marelan District, faces pressures from land conversion, limited yard size, and high dependence on food purchased from the market. On the other hand, the potential of unoptimized yard land and the existence of local farmer groups open up opportunities for empowerment strategies based on yard-scale plantation cultivation. This study aims to systematically examine the concept of farmer group empowerment, types of plantation crops that are appropriate to the characteristics of coastal agroecology, empowerment strategies and stages, and their contribution to food security in Paya Pasir Village. The study used a literature review method (library research) with a descriptive qualitative approach, reviewing accredited journal articles, community service results, and policy documents published between 2013 and 2026 through the Google Scholar, Garuda, and DOAJ databases. The study results indicate that empowering farmer groups through the cultivation of plantation crops such as coconut, citronella, betel nut, cocoa, and pepper in their yards can increase the diversification of food sources and household income if supported by ongoing extension, strengthening group institutions, and cross-sector partnerships. The main inhibiting factors include limited technical cultivation knowledge, sandy soil conditions and high salinity typical of coastal areas, minimal access to capital, and weak ongoing mentoring. This study recommends a phased empowerment model that integrates institutional capacity building, the introduction of appropriate cultivation technologies, and diversification of economically valuable plantation crops as a path towards sustainable family and community food security in Paya Pasir Village.